2002
DOI: 10.1046/j.1365-2842.2002.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary examination of patients with illness attributed to dental fillings

Abstract: The results do not support the hypothesis that release of mercury from amalgam fillings is the cause of 'amalgam disease', but suggest that there may be various explanations for the patient's complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 22 publications
(22 reference statements)
7
43
1
1
Order By: Relevance
“…Multiple human studies, however, have failed to establish causation [74][75][76][77][78][79][80][81]. Some studies have reported improvement in a variety of symptoms after the removal of mercury amalgam; however, these studies have not clearly established a link between amalgam removal and improvement of symptoms [82,83]. It should be noted that removal of mercury amalgam appears to increase plasma mercury by three-to fourfold for a short time after removal [84,85].…”
Section: Dental Amalgammentioning
confidence: 99%
“…Multiple human studies, however, have failed to establish causation [74][75][76][77][78][79][80][81]. Some studies have reported improvement in a variety of symptoms after the removal of mercury amalgam; however, these studies have not clearly established a link between amalgam removal and improvement of symptoms [82,83]. It should be noted that removal of mercury amalgam appears to increase plasma mercury by three-to fourfold for a short time after removal [84,85].…”
Section: Dental Amalgammentioning
confidence: 99%
“…It has been feared that mercury in amalgam may cause a variety of symptoms. This so-called 'amalgam disease' is however controversial, and although some authors claim proof of symptom relief after removal of dental amalgam fillings (Lindh et al, 2002); there is no scientific evidence of this (Langworth et al, 2002). Mercury exposure affects the central nervous system, brain functions, causes DNA and chromosomal damage, and causes reproductive problems.…”
Section: Toxicology Of Mercurymentioning
confidence: 99%
“…So far there is no convincing evidence from epidemiological, toxicological or immunological research that 'amalgam burden' or 'amalgam hypersensitivity' (beyond rare cases of proven allergic reactions like oral lichenoid reactions) are valid pathological concepts [1,2]. Nevertheless many patients and physicians are convinced that amalgam is hazardous to health [3,4]. In 1996, a group of about 1,500 patients who attributed their chronic complaints to amalgam fillings filed a lawsuit against Degussa, the major German manufacturer of this material.…”
Section: Introductionmentioning
confidence: 99%